One-Flow Operation via 4-Bromopyridine Enables Flash Synthesis of AChE Inhibitor - Soutome, Hiroki; Kimuro, Yusuke; Kawaguchi, Tomoko; Yoo, Dong-eun; Yao, Yiyue; Oshida, Shuto; Nakayama, Hiroki; Iwata, Masatomo; Ebisawa, Ruka; Kikuchi, Ryuhei; Tomite, Kyosuke; Wada, Shuto; Ashikari, Yosuke; Nagaki, Aiichiro (Synthesis, 2024)
4-Bromopyridine is a building block that can be converted into valuable compounds, but due to its low stability, it is commercially available in the form of hydrochloride salt. Therefore, the hydrochloride salt is usually desalted with a basic aqueous solution and dried before organic reaction. In this study, to simplify the preparation and reaction procedure of 4-bromopyridine, multiple operations, desalting with a base, separation of the aqueous layer, and subsequent halogen–lithium exchange reaction were integrated into a single flow reaction. The reaction sequence was completed within 20 seconds and the yields were higher than the conventional methods. This is because the subsequent reaction can be performed immediately after the generation of 4-bromopyridine, which is unstable under ambient conditions.
Keywords: one flow operation; flow microreactors; flash chemistry; integrated flow reactions; bromopyridine hydrochloride; liquid-liquid separate membrane; AChE inhibitors